2017
DOI: 10.3233/wor-172597
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and return to work after mild/moderate traumatic brain injury: A systematic review

Abstract: Abstract. BACKGROUND:Approximately two percent of the United States population are traumatic brain injury (TBI) survivors. The unemployment rate among them is substantial. Cognitive skills are essential to perform any job. OBJECTIVE: We analyzed the literature on cognitive rehabilitation (CR) related to mild/moderate TBI to learn the influence of cognition on return to work (RTW) post TBI. METHODS:We conducted a systematic review of the studies on CR related to RTW post TBI that were published between 2000 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 54 publications
1
30
1
2
Order By: Relevance
“…Looking more specifically at productivity loss, Silverberg et al (13) found that residual symptoms and comorbid psychiatric conditions were predictors, and regarding long-term outcomes, Theadom et al (11) reported that cognitive complaints at 1 month post-injury were predictive of work limitations 4 years post-injury. A recent systematic review supports the role of cognition in predicting and facilitating RTW (17). Thus, a range of factors, including demographic, physical, cognitive, and emotional as well as environmental and societal, may impact the course of employment outcomes after mTBI in a complex interaction, which is yet unclear.…”
Section: Introductionmentioning
confidence: 90%
“…Looking more specifically at productivity loss, Silverberg et al (13) found that residual symptoms and comorbid psychiatric conditions were predictors, and regarding long-term outcomes, Theadom et al (11) reported that cognitive complaints at 1 month post-injury were predictive of work limitations 4 years post-injury. A recent systematic review supports the role of cognition in predicting and facilitating RTW (17). Thus, a range of factors, including demographic, physical, cognitive, and emotional as well as environmental and societal, may impact the course of employment outcomes after mTBI in a complex interaction, which is yet unclear.…”
Section: Introductionmentioning
confidence: 90%
“…Traumatic brain injury (TBI) causes damaging neurological impairments leading to disability and morbidity. TBI affects young and old, with young victims creating a substantial negative impact to families and wider society with years of lost productivity and an increasing burden on healthcare systems [1,2]. Such is its prevalence that its economic cost to the US is $56 billion a year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive deficits are common after TBI and have consistently been linked to negative employment outcome (15,22,23). Cognitive skills such as learning new tasks, and social interaction at the workplace are crucial for job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive skills such as learning new tasks, and social interaction at the workplace are crucial for job performance. A literature review by Mani and colleagues (22) found that executive functioning, attention, memory, and verbal skills were predictive of RTW post-TBI. The review also found evidence for the efficacy of cognitive rehabilitation in facilitating RTW.…”
Section: Introductionmentioning
confidence: 99%